AGING EFFECTS ON TRANSFORMATION TEMPERATURES AND ENTHALPIES FOR TiNi ALLOY - Canbay, Canan Aksu; Özkul, İskender (My University, 2018)
Shape memory alloys are frequently used today. For this reason, researches are more focused on this subject. In this study,transformation temperature and enthalpy changes caused by aging of TiNi alloy were investigated from thermally inducedshape memory alloys. The results obtained from the experiments performed in 21 different aging environments wereevaluated by using graphs. The results showed us how effective the variable parameters used in the experiments are on thealloy.
Keywords: Malzeme Bilimleri; Özellik ve Test; Mühendislik; Kimya